2002
DOI: 10.1046/j.1365-2435.2002.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in ant and rodent post‐dispersal predation of vertebrate‐dispersed seeds

Abstract: Summary1. Post-dispersal predation of vertebrate-dispersed seeds has received little attention in the Mediterranean region. We investigated the spatial variation in post-dispersal seed predation of vertebrate-dispersed plants and its potential implications for plant diversity in fleshy fruited plant communities of southern Spain.2. An experiment was conducted in forests and open scrubland at mid-and high elevations to explore: (a) the possibility of differential seed predation by rodents and granivorous ants; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 47 publications
(91 reference statements)
2
65
3
1
Order By: Relevance
“…Our study failed to find evidence for either of these mechanisms, suggesting that differential predation of seeds or seedlings does not contribute to seedling bank diversity in our study system. Rey et al (2002) also found little variation in predator seed preferences across habitats in sites that coincided with lowered plant diversity. In addition, they found that rodents displayed no preference for larger-seeded species, while ants actually preferred smaller-seeded species.…”
Section: Discussionmentioning
confidence: 89%
“…Our study failed to find evidence for either of these mechanisms, suggesting that differential predation of seeds or seedlings does not contribute to seedling bank diversity in our study system. Rey et al (2002) also found little variation in predator seed preferences across habitats in sites that coincided with lowered plant diversity. In addition, they found that rodents displayed no preference for larger-seeded species, while ants actually preferred smaller-seeded species.…”
Section: Discussionmentioning
confidence: 89%
“…Seeds may be predated by a wide variety of animals, but predominantly by rodents, birds and ants (Brown et al 1979;Willson 1992;. Given the major activity of granivorous ants in Mediterranean open areas, even compared to rodent activity (Hulme 1997;Rey et al 2002;Boulay et al 2009), ants are considered the major predators of dry-fruited seeds in Mediterranean ecosystems (Willott et al 2000;Azcárate et al 2005). For this reason, a strong interaction between dry-fruited shrubs and seed-harvesting ants might be expected in Mediterranean grasslands and scrublands.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos que investigam a variação dos mecanismos de dispersão ao longo dos diferentes estratos verticais no nível de comunidades são escassos, pois a maioria se detém a observar um único mecanismo, espécie, ou outros fatores locais e infl uências (Drezner et al 2001Rey et al 2002. Wikander (1984) relatou que, em uma fl oresta decídua na Venezuela, a anemocoria foi a síndrome mais relevante, principalmente no estrato superior, e a zoocoria no inferior.…”
Section: Introductionunclassified